A systematic review of the psychological capital (PsyCap) research development: implementation and gaps - Burhanuddin, Nur Aimi Nasuha; Ahmad, Nor Aniza; Said, Rozita @ Radhiah; Asimiran, Soaib (Human Resource Management Academic Research Society, 2019)
A systematic review was conducted to investigate the literature on the psychological capital (PsyCap) research development. Four databases (ProQuest, EBSCOhost, Springer and Emerald Insight) were systematically searched to identify relevant articles published between 2008 and 2018. Findings revealed that research on PsyCap within educational organizations is still in its early stage. Most were done using quantitative methods with the emphasis given to the outcomes of the construct. This review highlighted that PsyCap was researched as predictor for a wide range of academic-related outcome such as engagement, motivation, achievement, performance, teachers’ job performance and attitude. This review will contribute to the continuing discussion on PsyCap in educational organization as well as useful to the researchers and policy makers in developing psychological resources within academe. The findings can be used in guiding future research needed to be conducted concerning PsyCap within educational organization by broadening the respondent to beyond teachers and students.